Modified Thermoelectric Coolers (TEC) Peltier Plate for Outdoor Activities with Rechargeable Battery using Solar Panel - Zakaria, Liana Fairuz; Mudin, Hatimi; M Nor, Fethma (Journal of Applied Science, Engineering and Technology, 2021)
Thermoelectric cooler box was designed with the purpose of cooling with thermoelectric cooler (TEC) Peltier plate as a cooling medium. The objective of this project was to invent a cooler box that is suitable for outdoor activities. The thermal conductivity which is to measure the ability of the material to conduct heat in each layer inside the thermoelectric cooler box was identified for heat transfer analysis. Thermoelectric cooler box can be operated with a 12V battery or 12V DC power supply. The battery power can be charged using a 20W solar panel (if the battery power is drained out), with the condition that there should be heat radiation to generate electricity. Thus, no additional cost is needed on ice cubes whereby previously it requires more ice cubes to maintain the cold temperature inside the cooler box. By using a Peltier plate, the cooling hours inside can reach up to 100,000 hours with a maximum of 12 can of beverages stored inside the cooling box. Based on literature reviews, conduction and convection resistance between each layer of materials inside the cooler box play an important role to ensure heat is transferred inside the box. The heat sink also helps to ensure heat dissipation before flowing into the cooler box. In this design, a total of 56 kW of heat can be transferred from the box to keep the cooler box cool with the minimum temperature 15.6°C within a period of 35 minutes.